Major intensification of Atlantic overturning circulation at the onset of Paleogene greenhouse warmth - S. J. Batenburg (Nature Portfolio, 2018)
Ocean circulation likely played a major role in past episodes of global warming. Here the authors show that converging neodymium isotope values indicate intensification of the Atlantic overturning circulation at 59 million years ago, which may have contributed to a more efficient distribution of heat over the planet.